Fluorescence Detection of Lead(II) Ions Through Their Induced Catalytic Activity of DNAzymes - Chi-Lin Li; Kung-Tien Liu; Yang‐Wei Lin; Huan‐Tsung Chang (2010)
We have developed a fluorescence approach for the highly selective and sensitive detection of Pb2+ ions using AGRO100, a G-quadruplex DNAzyme. The sensing strategy is based on Pb2+ ions inducing increased DNAzyme activity of AGRO100 in the presence of hemin, which acts as a cofactor to catalyze H2O2-mediated oxidation of Amplex UltraRed (AUR). A test of eight aptamers of various sequences for the detection of Pb2+ ions revealed that AGRO100 performed the best in terms of sensitivity. The AGRO100-AUR probe exhibited high selectivity (>100-fold) toward Pb2+ ions over other tested metal ions. The fluorescence intensity (excitation/emission maxima, ca. 561/592 nm) of the AUR product was proportional to the concentration of Pb2+ ions over the range 0−1000 nM, with a linear correlation (R2 = 0.98). For 5 mM Tris−acetate (pH 7.4) solutions in the presence and absence of 100 mM NaCl, the AGRO100-AUR probe provided limits of detection (signal-to-noise ratio = 3) for Pb2+ ions of 1.0 and 0.4 nM, respectively. We validated the practicality of the use of the AGRO100-AUR probe for the determination of the concentrations of Pb2+ ions in soil samples. This approach allows the determination of the concentrations of Pb2+ ions with simplicity, selectivity, and sensitivity.